Generational Dynamics in Social Media: Harnessing Instagram for Value Co-Creation in Tourism - Kemala Sari, Mareta; Prima Lita, Ratni Prima Lita; Lenggogeni, Sari; Ma’ruf Ma’ruf (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
This study analyzes how the influence of social media as a form of smart tourism technology (STT) affects the formation of value co-creation (VCC) in the home base accommodation industry. Furthermore, to see whether gender and generation become control variables in the relationship between smart tourism technology and value co-creation, is the purpose of this study. This study was conducted with a quantitative descriptive method. Conducted on 135 tourists in 17 home base accommodation destinations in West Sumatra, collecting data through official accounts of tourist destination managers. Partial least squares structural equation modeling and SPSS V.24 were used to analyze data and test hypotheses. The results found, where smart tourism technology has a positive and significant influence on value co-creation. Through social media, as a form of smart tourism technology, destination management organizations are able to involve tourists as co-producers in creating a sense of pleasure and an unforgettable experience. Gender does not moderate the effect of STT on VCC. The generation variable, is a moderating variable between STT and VCC. where generation strengthens the relationship between STT and VCC.